Desain lembar kerja siswa berbasis discovery learning terintegrasi PhET simulation untuk Meningkatkan Keterampilan Proses Sains Peserta Didik pada materi Hukum Ohm - Buhera, Rusdiman; Sri Bona Ayu; Luqmanul H. A. Abdillah; Nurohman, Sabar (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
This development was motivated by students' low science process skills and the limited availability of teaching materials that integrate simulation technology in junior high school science learning, necessitating innovation in the form of worksheets that can facilitate discovery-based learning. This research employed the Research and Development (R&D) methodology with the ADDIE model. A pre-experimental design with one group pretest-posttest was used at the implementation stage. The research subjects were ninth-grade students. Data was collected through validation sheets for experts and practitioners, student response questionnaires for readability testing, and science process skills test instruments in multiple-choice questions. Data analysis used quantitative descriptive techniques for validation and readability data, while N-gain test and nonparametric statistical analysis with the Wilcoxon test to analyze product effectiveness. Product feasibility assessment involved media experts, content experts, two practitioners, and 10 ninth-grade students selected through purposive sampling considering different academic ability levels to assess readability. The results showed very high product validity, with average scores of 0.83 from experts and 0.97 from practitioners. The readability test achieved 96%, falling into the excellent category. Product effectiveness was proven high, with an N-gain of 0.85. The Wilcoxon signed-rank test yielded a p-value < 0.05, indicating a significant improvement in students' science process skills. Developing technology-based teaching materials can provide alternative solutions for teachers in integrating virtual practicum into science learning to improve students' science process skills.